Quality of Life during chemotherapy: implications for social and legal medicine - Massoni, Francesco; Ricci, Pasquale; Ricciardi, Max Rapp; Luzi, Eleonora; Archer, Trevor; Ricci, Serafino (European Journal of Oncology and Environmental Health, 2015)
The impact of chemotherapy on Quality of Life (QoL) of cancer patients is much discussed in the literature and as common in many countries also in Italy the legislation provides an economic benefit in the case of citizens with incapacity in the performance of activities of daily living. The authors present a study designed to assess the degree to which chemotherapy affect QoL of cancer patients also in function of variables as age, gender or type of cancer. The sample consisted of sixty three patients receiving chemotherapy (20/63 M and 43/63 F; age 18-87) while the control group of fifty eight cancer patients not in chemotherapy (36/58 M and 22/58 F; age 30-85). There is a statistically significant association between chemotherapy and incapacity in the performance of activities of daily living (OR 5.28; CI 95%: 2.28-12.26; p